Analysis of mechanical grooming at various frequencies on a large scale test panel coated with a fouling-release coating. Issue 5 (27th May 2016) - Hearin, John; Hunsucker, Kelli Z.; Swain, Geoffrey; Gardner, Harrison; Stephens, Abraham; Lieberman, Kody
Abstract: A mechanical grooming test was performed on large scale steel test panels coated with a fouling-release (FR) coating (International Intersleek 900), at four different frequencies, during the high fouling season in Port Canaveral, Florida. Grooming at frequencies of three or two times per week was effective at removing heavy biofilm growth and significantly reduced macrofouling settlement. Mechanical grooming at lower frequencies of weekly or bi-weekly removed heavy biofilm growth but was much less effective at reducing macrofouling settlement. The results indicated that frequent mechanical grooming could reduce the fouling rating of ships coated with FR coatings. The reduction in the fouling rating of ships' hulls by frequent grooming could offer significant reductions in drag, fuel consumption, and the emission of exhaust gases. Frequent grooming could also eliminate the need for hull cleaning and increase the time between dry docking which would reduce the operational costs for many vessel operators.